Impunity entrenched: the erosion of human rights in the UK. (April 2022) - Webber, Frances
In this article, the author provides a roundup of the UK Conservative government's legislative programme in 2021, arguing that, in the service of an authoritarian agenda, it uses law to undermine the rule of law and executive accountability, and to criminalise marginalised and/or racialised groups, including asylum seekers and those helping them, black youth, protesters and human rights defenders, and Gypsies, Roma and Travellers. Through an analysis of various new bills that attack human and civil rights, including the Police, Crime, Sentencing and Courts Bill, the Nationality and Borders Bill, the Overseas Operations Act, the Elections Bill and the Judicial Review and Courts Bill, she demonstrates the cumulative impact of the legislative programme that has entrenched the demonisation of minorities and human rights defenders, whilst giving unprecedented powers to police, hobbling the courts, nobbling other regulators and blocking effective legal, political and public accountability for ministers. The result, she argues, is an erosion of human rights and the entrenchment of impunity for the government and its agencies.